Historični seminar 13 - Žagar Karer, Mojca; Šter, Katarina (ZRC SAZU, Založba ZRC, 2018)
The volume Historični seminar 13 ('Historical Seminar 13') offers a selection of articles that have been "filtered" through the cycle of lectures over the past two years. These articles were written by ten researchers from Slovenia, Austria, Croatia, and Germany. Historični seminar 13 continues to examine its origin in the humanities by looking at history and describing the past, with perspectives that are also directed toward other disciplines: geography, comparative literature, ethnomusicology, and cultural anthropology. However, it always maintains a critical distance, which is emphasized in various ways because many of the articles question previous assumptions of past studies and their subjective points of departure. In this manner, this volume makes an important contribution to critical thought about scholarship in general and about the future tasks of the humanities and the social sciences. At the same time, it adds an increasingly current ethical touch to much of its material. Historični seminar 13 is freely available online.